Efektivitas Intervensi Non-Farmakologis dalam Mengurangi Nyeri Haid: Sebuah Studi Literatur - Ernawati Ernawati; M. Askar M. Askar (Media Kesehatan Politeknik Kesehatan Makassar, 2024)
Primary dysmenorrhea is a common reproductive health issue among women that can disrupt daily activities. Pharmacological treatments often cause side effects, making non-pharmacological interventions an appealing alternative. This study aimed to evaluate the effectiveness of non-pharmacological interventions, such as heat therapy, yoga, exercise, acupressure, effleurage massage, and lifestyle modifications, in reducing menstrual pain. A systematic review approach was employed, analyzing 16 relevant articles. Results showed that all methods significantly reduced pain levels, with yoga and exercise yielding the greatest reduction (2.8–3 points on the VAS scale). Heat therapy, acupressure, and effleurage massage provided immediate but temporary relief. Lifestyle modifications offered long-term benefits in improving quality of life. Combining methods is recommended for optimal outcomes.